Skeletal Muscle Protein Balance and Metabolism in the Elderly - S. Fry, Christopher; B. Rasmussen, Blake (Current Aging Science, 2011)
The loss of lean muscle mass occurring with advancing age is termed sarcopenia. This condition often leads to a concomitant loss of strength, increased frailty and risk of falls and an overall loss of functional independence in the elderly. Muscle protein metabolism is a dynamic process characterized by the balance between the synthesis and breakdown of muscle proteins. A disturbance of this equilibrium can lead to the loss of muscle mass, and a perturbation of muscle protein turnover with aging has been proposed to play a role in the development of sarcopenia. However, basal muscle protein synthesis and breakdown rates do not differ between young and old adults, which has led to the hypothesis that older adults are resistant to anabolic stimuli. In support of this hypothesis, older adults have either no response or a blunted response to nutrients, insulin and resistance exercise, and this anabolic resistance is likely a key factor in the loss of skeletal muscle mass with aging. Recent studies have investigated potential interventions to overcome this anabolic resistance. In particular, combining resistance exercise with essential amino acid supplementation restores the muscle protein anabolic response in older men. The novel rehabilitation technique of performing light resistance exercise during blood flow restriction was also successful in overcoming the anabolic resistance to exercise. Future research is needed to determine whether these novel interventions will be successful in preventing sarcopenia and improving muscle strength and function in older adults.
Keywords: mTOR